2007
DOI: 10.1253/circj.71.a20
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Vein Arrhythmias

Abstract: The thoracic veins are important foci for the genesis of ectopic atrial tachycardia and play a critical role in the pathophysiology of paroxysmal and permanent atrial fibrillation. The pulmonary veins have the highest arrhythmogenic activity and other venous structures (eg, superior vena cava, coronary sinus and ligament of Marshall) have also been shown arrhythmogenic potential. Thoracic veins contain cardiomyocytes with distinct electrical activities and complex anatomical structures. This review summaries t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Atrial arrhythmia can originate at the pulmonary veins [ 69 ]. Other veinous structures have also been found to serve as the initiation sites for arrhythmias [ 70 ]. The simulations shown here demonstrate how a reduction in the dimensionality of the system can lower the number of myocytes needed for the generation of an arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial arrhythmia can originate at the pulmonary veins [ 69 ]. Other veinous structures have also been found to serve as the initiation sites for arrhythmias [ 70 ]. The simulations shown here demonstrate how a reduction in the dimensionality of the system can lower the number of myocytes needed for the generation of an arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, the challenges inherent in approaching LV summit arrhythmias accounts for the majority of OT VA procedural failures in the present era. Alternative ablation techniques such as intracoronary ethanol infusion may provide enhanced procedural success in selected patients …”
Section: Specific Challengesmentioning
confidence: 99%
“…Premature atrial contraction that triggers AF is not always identified during procedures, and a proportion of trigger ectopics originate from non-PV regions [10,11]. In such cases, additional ablation of non-PV foci has demonstrated efficacy in improving AFfree survival; however, there is a lack of consensus regarding the most appropriate method for identifying non-PV foci.…”
Section: Introductionmentioning
confidence: 99%